2022
DOI: 10.7759/cureus.31535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Critical Appraisal Skills by Introducing Journal Clubs to Preclinical Dental Students Using the Assessing Competency in Evidence-Based Medicine (ACE) Tool Through Pre and Post-testing

Abstract: BackgroundThe ineffective utilization of journal clubs (JCs) for pre-clinical dental students has led to a lack of research into their effectiveness in developing skills such as critical reasoning and evidence-based medicine (EBM) practice. Therefore, we have implemented JCs in first-year undergraduate dental students and measured their effectiveness using the integrated Assessing Competency in Evidence-Based Medicine (ACE) tool. MethodologyWe conducted a quasi-experimental study where EBM was included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Most of the selected studies originated from North America, 27–30,33,38,40,41 followed by Middle‐Eastern universities 6,35,36,39,46 . Fourteen studies evaluated changes observed in a single group of participants after the implementation of an educational intervention, with no comparative analyses 6,27–30,32,37,39–44,46 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the selected studies originated from North America, 27–30,33,38,40,41 followed by Middle‐Eastern universities 6,35,36,39,46 . Fourteen studies evaluated changes observed in a single group of participants after the implementation of an educational intervention, with no comparative analyses 6,27–30,32,37,39–44,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the selected studies originated from North America, 27–30,33,38,40,41 followed by Middle‐Eastern universities 6,35,36,39,46 . Fourteen studies evaluated changes observed in a single group of participants after the implementation of an educational intervention, with no comparative analyses 6,27–30,32,37,39–44,46 . Alternatively, five studies compared parallel cohorts, 31,34–36,38,45 wherein either different educational interventions were comparatively evaluated, 31,34,38 or trained were compared with untrained students 35,36,45 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations